Portfolio framework for recognition prior learning for technical programmes in Malaysia - Kaprawi, Noraini (2010)
The objective of this reseach is to identify major domains and the necessary criteria in generating a Portfolio Framework for Recognition of Prior Learning (RPL) and to design a portfolio framework for the RPL for technical programmes in Malaysia. This quantitative research is based on document analysis, questionnaire and interviews of experts. About 28 experts from nine public and private institutions of higher learning (IHLs) have been chosen as the key respondents to undertake the questionnaires while a few RPL experts were selected for the interviews. The represented institutions involved in this research includes Malaysian Qualification Agency (MQA), Ministry of Higher Education, Universiti Tun Hussein Onn Malaysia (UTHM), The Open University Malaysia (OUM), Universiti Kuala Lumpur (UniKL), Institut Latihan Perindustrian (ILP), Ministry of Human Resource and industries. The result from this research indicated that there are seven domains required in the development of portfolio; namely candidate's profile, academic qualifications, nonacademic qualification, prior learning courses attended, latest skills acquired, generic skills, and academic skills and work experience attestation. The findings may be used as guidelines for RPL assessment performance in Malaysia.